(untitled) (Global Journal of Human-Social Science, 2024)
The research Mapping and Characterization of the Physical-Natural Units of the Municipality of Massap Cear aims to shed light on the geographical and environmental richness of the backcountry region of northeastern Brazil exploring the complexity of the northeastern hinterland In this way it covers the mapping of physical-natural units in the municipality of Massap in the state of Cear considering its importance for territorial planning and environmental management the characterization of the nature of the municipality allows the understanding of the dynamics and interactions between the environment and the human activities providing relevant data for preservation and sustainable development strategies It is concluded that the research contributes significantly to the integrated understanding of the geographic space in question providing valuable information for the reader s knowledge and for the preservation of its geodiversity and sustainable management of the region